Stabilisation of plasma welding arcs by low power laser beams. (May 2013) - Mahrle, A; Rose, S; Schnick, M; Beyer, E; Füssel, U
Abstract : Results of an experimental study are presented in which the impact of a low power laser beam on the stability behaviour of plasma arcs was investigated. Both heat sources were arranged in a recently developed coaxial set-up. Bead on plate welding trials on AISI 304 stainless steel sheets demonstrated that the additional laser beam is capable of extending existing limitations of low current plasma arc welding processes with respect to realisable welding speeds. In particular, an effective stabilisation of the anodic arc attachment under conditions of direct current electrode negative plasma arc welding was achieved by use of a laser beam with only 100 W output power. As a result of a performed stability analysis, the particular conditions for arc stabilisation are specified and conclusions about the most probable physical reasons for the stabilising action of the laser beam are drawn.